PENERAPAN METODE BERMAIN PERAN BERBANTUAN KOMIK TATAKRAMA BASA SUNDA - Nurjanah, Ineu; Dadan Djuanda; Diah Gusrayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the implementation of the role-playing method supported by Sundanese etiquette comics in improving students' etiquette skills. This study is motivated by students’ low ability to apply Sundanese etiquette, influenced by an environment that rarely encourages the use of Sundanese and the mixing of Sundanese with Indonesian. The research employed a convergent mixed-methods design. On the quantitative side, a quasi-experimental design with a pretest-posttest non-equivalent control group model was used, where two groups of students (control and experimental) were compared to observe learning improvement after treatment. Meanwhile, the qualitative component explored in depth the responses, experiences, and perspectives of both students and teachers regarding the learning process. The subjects consisted of two classes, namely the control class at SDN Citungku and the experimental class at SDN Ganjartemu. Research instruments included pretest and posttest, student response questionnaires, observation sheets, and interview guides. The results indicated that the implementation of the role-playing method assisted by Sundanese etiquette comics significantly improved students’ etiquette skills compared to the control class. These findings suggest that using the role-playing method supported by comic media can serve as an effective learning strategy to enhance elementary students’ mastery of Sundanese etiquette.